Analysis of abnormalities in pituitary gland in non-missile head injury: study of 100 consecutive cases. Issue 7 (July 1986) - Harper, C G; Doyle, D; Adams, J H; Graham, D I
Abstract : Pituitary glands, obtained at necropsy from a consecutive series of 100 patients who had died as a result of non-missile head injuries, were examined to define the incidence and pathogenesis of abnormality.